Experimental investigation of heat spreading in a wickless and ultrathin thermal ground plane. (March 2022) - Wang, Xiaomeng; Moon, Joo Hyun; Fadda, Dani; Shin, Dong Hwan; Lee, Jungho; You, Seung M.
Abstract: A thermal ground plane (TGP) device spreads concentrated heat effectively into a relatively large area. The TGP selected for this study utilizes bubble pumping, instead of wicking, to effectively circulate fluid inside its chamber and keep the hot area wetted. It is thin, light, durable, and its performance is orientation-independent. With a 0.80 mm thick chamber, this TGP can achieve a thermal resistance below 0.2 K/W. Reducing the chamber's thickness by 20% and 50% is shown experimentally to yield a better thermal resistance, as low as 0.15 K/W. The corresponding maximum effective thermal conductivity of the TGP is 1339 W/m-K, 1008 W/m-K, and 821 W/m-K for a chamber thickness of 0.40 mm, 0.64 mm, 0.80 mm, respectively. However, a reduced dryout heat flux is detected with a thinner TGP. This work aims to investigate the effects of the chamber's thickness on the thermal performance of this ultrathin TGP. The performance of the TGP is orientation-independent regardless of thickness and water charging amount in its chamber.